Extracts of Gnetumafricanum(Gnetacae) Ameliorated Liver Injuries of Cyclophosphamide Immunosuppressed Rats. - Madubogwu, Ngozi; Unekwe, Prince c.; Erhirhie, Earnest; Okoye, Festus B.C (Journal of Current Biomedical Research, 2022)
Gnetum africanum(Gnatacae) is a ceremonial delicacy in many parts of Eastern Nigeria and the leaves are either eaten raw or are finely shredded and added to soup.The effect of cyclophosphamide (CP) administration on the liver biomarkers of albino rats and the possible protective role of G.africanum extract was studied. Thirty rats were randomly divided into six groups of five rats each. Groups I-V were injected intraperitoneally with 70 mg/kg of CP on the first day while group VI was not injected with cyclophosphamide. Group I received 10 mL/kg of distilled water orally. Groups II, III and IV received daily dose of 50, 100and 200 mg/kg of extract respectively and group V received levamisole (2.5 mg/kg) for 14 days. The rats were sacrificed 24h after thelast dose and blood samples collected through cardiac puncture into non-heparinized tubes, allowed to clot for 30 min and sera obtained was used for determination ofaspartate amino transaminase (AST), alanine amino transaminase (ALT) and alkaline phosphatase (ALP). Histopathology of rat liver was also carried out. Treatment with G. africanum ethanol extract produced significant (P<0.05) decrease in the values of ALT and AST while there were no significant changes (P>0.05) in ALP in Cyclophosphamide induced group. Histopathology examination of liver sections of untreated control group showed hypertrophied central vein with moderate purulent exudates accumulation while those treated with the extracts ameliorated the hepatic damage caused by CP. The present work revealed that G.africanum ethanol extract exerts liver protective effect in albino rats exposed to CP and may offer useful application as supplemental agent in the management of hepatic injuries arising from chemotherapy.